Peripartum Cardiomiopathy - Rizki Akbar; Cut Elvina Zuhra (Jurnal Anestesi, 2025)
Peripartum cardiomyopathy (PPCM) is a rare form of heart failure that occurs between the last month of pregnancy and up to five months postpartum. It is categorized as dilated cardiomyopathy, which impairs the systolic function of the left ventricle. Its incidence varies from 1:300 to 1:4000 pregnancies, influenced by genetic and cultural factors. The exact cause remains unknown, but it is believed to involve viral infections, autoimmune disorders, toxins, and micronutrient deficiencies. Key risk factors include advanced age, multiparity, multiple pregnancies, obesity, malnutrition, and substance abuse (alcohol and drugs). PPCM is more common in women over 30 years of age and those with a history of multiple pregnancies. Further research is needed to better understand the causes and mechanisms underlying this condition.